Enhancing Early Childhood Education through Effective School Leadership: The Impact of PAUD Principals on Teacher Welfare and Institutional Progress in Cangkuang Kulon, Kab. Bandung - Nurleni, Nurleni; Mulyaniapi, Tepi; Anwaruddin, Anwaruddin (Journal of Islamic Early Childhood Education (JOIECE): PIAUD-Ku, 2025)
The success of early childhood education institutions is undoubtedly linked to the role of the principal, who must possess the qualifications and competencies of a kindergarten/RA principal as stipulated by the Minister of Education. The performance of a principal will undoubtedly influence various components within an educational institution, including teacher welfare and the progress of early childhood education institutions. This study aims to determine the influence of the performance of PAUD principals in Cangkuang Kulon Village, Dayeuhkolot District, Bandung Regency on teacher welfare and PAUD progress. The research was conducted by collecting data from questionnaires distributed to 23 PAUD institutions with a total of 54 teacher respondents. This study obtained 74.1% of the data. PAUD principals in Cangkuang Kulon village showed continuous improvement in the quality of education, and PAUD teachers obtained welfare in accordance with the indicators as PAUD teachers, as seen from 64.8% of PAUD teachers always having a professional attitude in accordance with Law No. 14 of 2005 in facing work challenges. PAUD institutions are in line with PAUD institutional development indicators, as evidenced by 59.3%, indicating that PAUD institutions meet children's needs in terms of learning and physical activities.